PENGARUH PERSEPSI KEADILAN TERHADAP KEPUASAN, REKOMENDASI DARI MULUT KE MULUT, DAN NIAT MENGGUNAKAN KEMBALI - astuti, ni nyoman trivina (E-Jurnal Manajemen; Vol 1 No 2 (2012), 2012)
This study was conducted to elucidate the relationship between perceived fairness of complaint handling against patient’s satisfaction, word of mouth, and intention of re-using hospital services. Subjects were patients of Prima Medika Hospital, with a sample of 126 people. Determinations of sample are using purposive sampling or judgment sampling two stages. The data was then processed by using Structural Equation Modeling with AMOS support application tools. The results of this study suggest that perceptions of procedural fairness, distributive fairness, and interactional fairness has a positive and significant impact on patient satisfaction after complaints handling, word of mouth, and intention to re-use hospice services. Keywords: Intention of re-using, Perceived fairness, Satisfaction, Word of mouth